ASUHAN KEBIDANAN PADA IBU A DENGAN PENERAPAN MASSAGE PUNGGUNG UNTUK MENGURANGI NYERI PERSALINAN DI TPMB DEWI SANDRA KECAMATAN MEUREUBO KABUPATEN ACEH BARAT - Marhamah, Putri Rizki; Julianti, Rina; Zahara, Evi; Norisa, Nanda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Introduction: Labor pain is a phenomenon found in women who are in labor, but with a midwife's belief in midwifery philosophy, a midwife can provide high quality services for each phase, especially during the labor phase. There are many methods used to reduce pain during childbirth, one of which is back massage. Objective: This study aims to provide comprehensive midwifery care, especially to mother A with a history of normal delivery who experienced pain in the abdominal area that spread to the waist and back. Researchers used back massage techniques to reduce labor pain. Research method: this research is a case study with a qualitative descriptive approach. The research was carried out by exploring and providing comprehensive midwifery care to Mrs. A G1P0A0 starting from the third trimester of pregnancy until postpartum. Meanwhile, for labor pain in mothers, the method of measuring pain before and after massage is used. Research results: Comprehensive midwifery care for Mrs. A has been carried out from pregnancy to postpartum. In this birthing care, the researcher found the case of mother A G1P0A0 with pain during labor, so the researcher performed a back massage technique on mother A to reduce mother A's pain during labor. The results of the back massage technique are proven that this back massage technique really helps birthing mothers who experience pain during the birth process.Conclusion: The midwifery care provided to Mother A with pain during labor can be concluded that the application of back massage techniques to Mother A has been proven to reduce pain during labor. Mother A's delivery went smoothly and was not accompanied by any obstacles